BIRD ECOLOGY FROM THE RAVI RIVER OF LAHORE: HABITAT DEGRADATION - M. Iqbal; I. Saleem; Z. Ali; M. A. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2011)
The habitat degradation of the birds is determined from the five sites of the Ravi River near Lahore in this paper. The studied sites were surveyed from mid March to mid September in 2008 and found 22 species of the birds. Water samples were taken from the sites and the different selected parameters were used for water analysis including pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Chloride and Sulphate. The results revealed that all the values of pH, BOD, COD, TDS, TSS, Chloride and Sulphate exceeded the national environmental quality standard (NEQS) limits in the studied sites of the Ravi River near Lahore. The threats for the birds and the recommendations are discussed in this paper.
Keywords: Hadiara drain; Habitat degradation; Birds; Lahore; River Ravi.